Isolation and identification of protease‐producing bacteria from sludge and sediment soil around Adama, Ethiopia - Yeshaneh Adimasu Lemenh; Teshome Geremew Biru; Adinew Zewdu Chernet; Feleke Belachew Lema (Indonesian Journal of Biotechnology, 2021)
Proteases are enzymes used in industries such the production and processing of detergents, food, leather, and silk. The aim of this study was to isolate and identify protease‐producing bacteria from a sludge disposal site and from sediments. Soil samples were collected separately from the selected area. Samples weighing 1 g were serially diluted and spread onto skim milk agar. A total of 16 bacteria species were isolated from the study samples. Four bacterial isolates showed high proteolytic activity and were selected for enzymatic study based on their zone of proteolysis. The isolates were identified based on biochemical tests. The results indicated that the isolated bacteria were E. coli (99.69%), Pseudomonas putrefaciens (Shewanella putrefaciens) (91.61%), Bacillus carboniphilus (92.78%), and Lysinibacillus sphaericus (98.4%). The crude protease enzymes produced by these bacterial isolates showed promising results for application in dehairing and destaining as detergent additives. Bacillus carboniphilus showed the best level of activity and was selected as the most potent protease‐producing bacteria for both dehairing and destaining ability. Soils from sludge disposal sites and sediments from around tannery wastes could be good sources from which to isolate alkaline protease‐producing bacteria.